2012
DOI: 10.1002/mar.20522
|View full text |Cite
|
Sign up to set email alerts
|

“It's not Easy Being Green”: Exploring Green Creeds, Green Deeds, and Internal Environmental Locus of Control

Abstract: The authors report on the development of a novel construct, internal environmental locus of control (INELOC), which captures consumers' multifaceted attitudes pertaining to personal responsibility towards and ability to affect environmental outcomes. Using data gathered from a sample of consumers, the linkages between INELOC and a wide array of environmental behaviors were investigated. Exploratory and confirmatory factor analyses revealed four first-order dimensions ("green consumer," "activism," "advocate," … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(182 citation statements)
references
References 53 publications
(83 reference statements)
10
167
1
4
Order By: Relevance
“…In the present study, this relationship between both constructs was confirmed in the three subsamples of nationalities, which is consistent with some studies [86][87][88][89][90]. Therefore, in contrast to findings from other studies [82,91,92], there is a strong association between environmental attitude and ecological behaviour in all groups of study.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, this relationship between both constructs was confirmed in the three subsamples of nationalities, which is consistent with some studies [86][87][88][89][90]. Therefore, in contrast to findings from other studies [82,91,92], there is a strong association between environmental attitude and ecological behaviour in all groups of study.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Hence, the usual findings reveal either a moderate relationship between environmental attitude and behaviour [73][74][75][76][77], or a weak relationship [78][79][80][81]. Moreover, there are several studies that report no such relationship at all [82][83][84][85].…”
Section: Research Model and Hypotheses Testingmentioning
confidence: 99%
“…Schwepker and Cornwell (1991) demonstrated the importance of this variable for pro-environmental behavior and, more recently, Cleveland et al (2012) developed a measure of internal environmental locus of control associated with green consumer behavior. This variable, similar to PCE, measures consumers' perception of their ability to influence relevant outcomes.…”
Section: Research On Pce and Sustainable Consumptionmentioning
confidence: 99%
“…Until now, researchers have focused on norms, values and individual features derived from internal factors [13]. With respect to studies that analyze and define the effects of external factors on pro-environmental behavior, these are rare or only partial [14][15][16][17]. Therefore, in order to better understand the reasons for individual behavior, in addition to an awareness of the psychological factors involved, it is also necessary to understand the context in which they operate since circumstances impose behavioral patterns that lead to certain forms of conduct and inhibit others.…”
Section: Introductionmentioning
confidence: 99%